2016
DOI: 10.31871/wjrr.2.3.6
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of Causes, Management and Prevention of Childhood Diarrhoea among Nursing Mothers in Two Selected Primary Health Centers in Oyo State, Nigeria

Abstract: Diarrhoea is widely recognized as a major cause of childhood morbidity and mortality in many developing countries, particularly in sub-Saharan Africa. The objective of this study is to assess the knowledge of causes, management and prevention of diarrhoea among nursing mothers of under-two children in two selected primary health centers in Ibadan North Local Government, Oyo state. A descriptive non-experimental research design was used for the study. One hundred and sixty nursing mothers were selected from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…The care practices of caregivers as another central theme of this review was split into subthemes of prevention practices and management/treatment practices. Few crosssectional studies reported poor preventive practices [26, 55,19]. On the prevention practices of caregivers, regular hand washing was noted as a preventive measure [28,39,32,40].…”
Section: Care Practices Of Caregivers Regarding Diarrhoeal Conditions In Children Under Fivementioning
confidence: 99%
See 1 more Smart Citation
“…The care practices of caregivers as another central theme of this review was split into subthemes of prevention practices and management/treatment practices. Few crosssectional studies reported poor preventive practices [26, 55,19]. On the prevention practices of caregivers, regular hand washing was noted as a preventive measure [28,39,32,40].…”
Section: Care Practices Of Caregivers Regarding Diarrhoeal Conditions In Children Under Fivementioning
confidence: 99%
“…A few scored respondents to determine "good" or "poor" practice. Therefore, with the preventive measures mentioned, poor prevention was generally reported in Botswana [26] and Nigeria [55]. Generally, people know the importance of maintaining personal hygiene.…”
Section: Care Practices Of Caregivers In Ghana For Diarrhoeal Conditions In Children Under Five Years Of Agementioning
confidence: 99%